2018
DOI: 10.1186/s12859-018-2315-y
|View full text |Cite
|
Sign up to set email alerts
|

bioSyntax: syntax highlighting for computational biology

Abstract: BackgroundComputational biology requires the reading and comprehension of biological data files. Plain-text formats such as SAM, VCF, GTF, PDB and FASTA, often contain critical information which is obfuscated by the data structure complexity.ResultsbioSyntax (https://biosyntax.org/) is a freely available suite of biological syntax highlighting packages for vim, gedit, Sublime, VSCode, and less. bioSyntax improves the legibility of low-level biological data in the bioinformatics workspace.ConclusionbioSyntax su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…As multiple sequence alignment problems have no objective mathematical function to optimize, most practitioners modify the computed output manually, or ever perform de novo manual alignments. In our case, the multiple alignment was completed by hand using the bioSyntax [ 14 ] highlighting package in the vim editor. We found that although UTRs showed a few similarities within certain ranges, the 5’-UTR segments varied greatly within the first 1000 bases.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…As multiple sequence alignment problems have no objective mathematical function to optimize, most practitioners modify the computed output manually, or ever perform de novo manual alignments. In our case, the multiple alignment was completed by hand using the bioSyntax [ 14 ] highlighting package in the vim editor. We found that although UTRs showed a few similarities within certain ranges, the 5’-UTR segments varied greatly within the first 1000 bases.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The format of the lexer is not standardized and varies between text editors. PyMOL lexers are available for several text editors 16 . If a PyMOL lexer is unavailable, the Python lexer works modestly well with the pymolsnips library.…”
Section: Discussionmentioning
confidence: 99%
“…The software currently provides support for Clustal Omega 1.2.0 [24], MUSCLE 3.8.31 [25], MAFFT 7.312 [26], and T-Coffee 11 [27]; the user may use whichever they prefer, as long as it is already installed on their system. This was one of the first improvements made to L1PD, since previously the sequences had been manually aligned with the aid of bioSyntax [28]. It should be noted that bioSyntax has continued to be an incredibly useful tool for viewing files on a remote server.…”
Section: Probe Generationmentioning
confidence: 99%